2018
DOI: 10.1002/ecy.2502
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effect of mycorrhizae on biomass production efficiency exceeds their carbon cost in a fertilization experiment

Abstract: Biomass production efficiency (BPE), the ratio of biomass production to photosynthesis, varies greatly among ecosystems and typically increases with increasing nutrient availability. Reduced carbon partitioning to mycorrhizal fungi (i.e., per unit photosynthesis) is the hypothesized underlying mechanism, as mycorrhizal abundance and plant dependence on these symbionts typically decrease with increasing nutrient availability. In a mesocosm experiment with Zea mays, we investigated the effect of nitrogen (N) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 68 publications
5
49
2
Order By: Relevance
“…In summer 2016, the year before the present experiment, the same mesocosms had been used in an N × P experiment. This previous experiment showed that the growth of maize in these soils was strongly limited by P availability, while N was ample as N addition did not affect plant growth (Verlinden et al, ). Nonetheless, to ensure that plant growth was not limited by N supply, 95.5 kg N/ha (calcium nitrate; YaraLiva ® Calcinit ® , Yara B.V., Rotterdam‐Vlaardingen, The Netherlands) was added to each mesocosm on 20 July 2017.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…In summer 2016, the year before the present experiment, the same mesocosms had been used in an N × P experiment. This previous experiment showed that the growth of maize in these soils was strongly limited by P availability, while N was ample as N addition did not affect plant growth (Verlinden et al, ). Nonetheless, to ensure that plant growth was not limited by N supply, 95.5 kg N/ha (calcium nitrate; YaraLiva ® Calcinit ® , Yara B.V., Rotterdam‐Vlaardingen, The Netherlands) was added to each mesocosm on 20 July 2017.…”
Section: Methodsmentioning
confidence: 92%
“…The experiment was set up in a greenhouse in Sint‐Katelijne‐Waver (Belgium, 51°04′38″N, 4°32′05″E) and consisted of 30 mesocosms with insulated walls (1 m × 1.2 m × 0.6 m high), filled with nutrient‐poor experimental soil containing C 3 plant‐derived organic matter (same soil as in Verlinden et al, ). The homogenized mixture contained (a) sandy soil (Arenosol) originating from a pine forest in a nature reserve in Belgium with a texture of 95% sand and 5% silt, mixed with (b) white river sand and (c) a minor fraction of potting soil in a proportion of 72, 23 and 5 volume %, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations